2020
DOI: 10.1007/s10592-020-01276-4
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic movement results in hybridisation in impala in southern Africa

Abstract: SMM was partially funded by a Postdoctoral Fellowship from the Faculty of Natural and Agricultural Sciences of the University of Pretoria and latterly by a Clancey Trust Postdoctoral Fellowship. We thank Harvey Boulter, Southern Cross Private Game Reserve, Kamanjab, Namibia for genetic samples and the technical staff at the Onderstepoort Veterinary Genetics Laboratory for assistance with laboratory work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(61 reference statements)
1
3
0
Order By: Relevance
“…Consistent with this, we found two black-faced individuals carrying common impala mtDNA haplotypes, as was also found in an earlier study (Nersting and Arctander 2001). We therefore conclude that introgression occurred naturally under climatic conditions that brought the two subspecies into contact, rather than as a result of recent translocations of common impala to Namibia, which has been a concern for the genetic integrity of the subspecies (Miller et al 2020;Lorenzen and Siegismund 2004). This introgression might have contributed to the relatively high genetic diversity found in the black-faced impala, despite its recent low population size.…”
Section: A Synthesis Of the Evolutionary Processes Within The Impalasupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with this, we found two black-faced individuals carrying common impala mtDNA haplotypes, as was also found in an earlier study (Nersting and Arctander 2001). We therefore conclude that introgression occurred naturally under climatic conditions that brought the two subspecies into contact, rather than as a result of recent translocations of common impala to Namibia, which has been a concern for the genetic integrity of the subspecies (Miller et al 2020;Lorenzen and Siegismund 2004). This introgression might have contributed to the relatively high genetic diversity found in the black-faced impala, despite its recent low population size.…”
Section: A Synthesis Of the Evolutionary Processes Within The Impalasupporting
confidence: 91%
“…Previous studies using mtDNA concluded that the main genetic structure within the common impala is characterised by a separation of southern from eastern populations, and that eastern populations appeared to have a younger origin (Lorenzen, Arctander, and Siegismund 2006; Nersting and Arctander 2001). Microsatellite-based studies initially did not find any sign of hybridization between the common and the black-faced impala (Lorenzen and Siegismund 2004), but a recent study identified several recent hybrids in Etosha National Park and nearby private game reserves (Miller et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…My literature search uncovered 31 papers (out of 59 studies, 53%) that involved the introduction of non‐native species (Figure 2a ). Some of these cases involved intentional movement of organisms, such as the release of game‐farm birds for hunting purposes (Forcina et al, 2020 ), the stocking of fish populations with captive‐bred animals (Beheregaray et al, 2017 ; Bruce et al, 2020 ), or the translocation of large mammals between African game reserves (Grobler et al, 2018 ; Miller et al, 2020 ; van Wyk et al, 2019 ). Other human‐assisted translocations were unintentional, such as the transport of aquatic organisms in ship hulls (Oziolor et al, 2019 ) or plant seeds by cargo or passenger transport, sometimes resulting in cryptic invasions and hybridization events (Morais & Reichard, 2018 ).…”
Section: Mechanisms Of Anthropogenic Hybridizationmentioning
confidence: 99%
“…In the latter decades, the increasing attention to tourism by several African countries led to growing attention to protected areas and, if needed, to the reintroductions of species that became historically extinct in these regions [25,82,83]. Hybridization between distinct taxa is a common result of translocations in South Africa, where several genera such as Connochaetes and Aepyceros are involved [21,84]. The same threat is now spreading elsewhere, a case in point being the managed populations of two Taurotragus species in the same area in Senegal; one being the critically endangered Taurotragus derbianus derbianus whose genetic integrity is potentially threatened by the imported T. oryx oryx-fortunately in this case, no hybrids have yet been detected based on microsatellite markers [73].…”
Section: Translocations and Conservationmentioning
confidence: 99%